Application of saponin biosurfactant and its recovery in the MEUF process for removal of methyl violet from wastewater. (1st December 2017) - Samal, Kulbhushan; Das, Chandan; Mohanty, Kaustubha
Abstract: The potential of saponin, a biosurfactant, in the micellar enhanced ultrafiltration (MEUF) process was tested systematically for removal of methyl violet from wastewater. For this, the aqueous extract of reetha ( Sapindus mukorossi ) pericarp which contains saponin was used as the biosurfactant. First, the micellar solubilization of methyl violet in saponin micelles was investigated in terms of molar solubilization power ( SP ) of saponin. It was observed that the adsorption of methyl violet on the agglomerates of saponin micelles was mainly responsible for the enhanced solubilization. The Gibbs free energy of solubilization (calculated as −29.63 kJ mol −1 ) suggested that process was feasible and spontaneous. The MEUF experiments were performed in batch as well as continuous mode using saponin biosurfactant, and the effect of operating parameters on permeate flux and solute retention were evaluated. The removal of methyl violet in MEUF process was >99% achieved with 10 kDa polyethersulfone (PES) membrane for feed dye concentration of 250 mg L −1 at studied conditions. Finally, the saponin in permeate was recovered using n-heptane and n-butanol by solvent extraction process. The solvent n -butanol showed better extraction efficiency as compared to n-heptane for saponin extraction. Graphical abstract: Highlights: Saponin, a biosurfactant was derived from the pericarp of reetha fruit. Solubilization of methyl violet in saponin micelle was examined. Biosurfactant saponin was used in MEUF process for removal of methyl violet. Recovery of saponin was attempted using solvent extraction process. Removal of methyl violet was >99%.